2013
DOI: 10.1002/hyp.10097
|View full text |Cite
|
Sign up to set email alerts
|

Transpiration inQuercus subertrees under shallow water table conditions: the role of soil and groundwater

Abstract: Abstract:Water is one of the major environmental factors limiting plant growth and survival in the Mediterranean region. Quercus suber L. woodlands occupy vast areas in the Iberian Peninsula, frequently under shallow water table conditions. The relative magnitude of soil and groundwater uptake to supply transpiration is not easy to evaluate under these circumstances. We recently developed a conceptual framework for the functioning of the root system in Q. suber that simulates well tree transpiration, based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 63 publications
0
35
0
Order By: Relevance
“…Gou and Miller (2014) found that the water source for transpiration in a blue oak stand (Q. douglasii) in a California savanna turned from soil water in the wet season to groundwater in the dry season. Similar results had been found in a Scots pine stand (P. sylvestris) in a sandy soil with shallow water table that the contribution of groundwater to transpiration from May to November reached 61%, while the groundwater contributed to 98.5% during the drought period in June (Vincke and Thiry, 2008), and in a cork oak woodland (Quercus suber) in the Mediterranean region where the yearly groundwater contribution to tree transpiration occupied by 30.3%, while groundwater uptake accounted for 72.3% in dry summer (Pinto et al, 2014). The critical role of groundwater is especially significant for shelterbelt under dry conditions.…”
Section: Contributions and Implications Of This Studymentioning
confidence: 98%
“…Gou and Miller (2014) found that the water source for transpiration in a blue oak stand (Q. douglasii) in a California savanna turned from soil water in the wet season to groundwater in the dry season. Similar results had been found in a Scots pine stand (P. sylvestris) in a sandy soil with shallow water table that the contribution of groundwater to transpiration from May to November reached 61%, while the groundwater contributed to 98.5% during the drought period in June (Vincke and Thiry, 2008), and in a cork oak woodland (Quercus suber) in the Mediterranean region where the yearly groundwater contribution to tree transpiration occupied by 30.3%, while groundwater uptake accounted for 72.3% in dry summer (Pinto et al, 2014). The critical role of groundwater is especially significant for shelterbelt under dry conditions.…”
Section: Contributions and Implications Of This Studymentioning
confidence: 98%
“…Their results indicated that the groundwater uptake accounted for 19% of tree transpiration during the growing season of 2013 in the same area as our study. Pinto et al (2013) estimated the yearly groundwater contribution to the transpiration of Quercus suber to be 30.3%, whereas groundwater uptake became dominant in the dry summer to account for 73.2% of the transpiration. The contribution of groundwater to tree transpiration varied with rainfall conditions.…”
Section: Water Sources Used In Shelterbelt Tree Transpirationmentioning
confidence: 99%
“…For this particular purpose, both spatial surveys and modelling are important. Several models are available to estimate the dynamics of groundwater use by tree transpiration (Gou & Miller, 2014;Orellana et al, 2014;Pinto et al, 2014). The large-scale mapping of zones where roots might have or not access to groundwater (groundwater dependent ecosystems) has been most frequently done indirectly, through remote sensing techniques coupled with geographic information systems (Howard & Merrifield, 2010;Gou et al, 2015;Yin et al, 2015).…”
Section: Examples Of Some Of the Possible Approaches To Better Adapt mentioning
confidence: 99%